2017
DOI: 10.1021/acs.chemmater.7b01438
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Scalable One-Step Method for Amination of Graphene Using Leuckart Reaction

Abstract: A very simple method of reductive amination, based on the Leuckart reaction, is reported. This method enables not only the reduction of graphite oxide, but also results in reduced graphene oxide functionalized with amine groups, where the amination degree is 3.2 at.% as determined by XPS. The dominant nitrogen functional group was primary amine, but pyridines and lactam groups were also observed. It was found that the aminofunctionalized reduced graphene oxide is a semimetallic material because of the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 71 publications
3
40
1
Order By: Relevance
“…The presence of enough water is essential for gel formation as in water NH 4 HCO 2 would dissolve and generate NH 4 OH and HCOOH. It was reported that heating ammonium formate with dry GO for several hours results in multi‐layered graphite‐like solid aminated graphene oxide while we obtained processable hydrogels after a minute of bath sonication for reactions employing concentrated GO dispersions.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The presence of enough water is essential for gel formation as in water NH 4 HCO 2 would dissolve and generate NH 4 OH and HCOOH. It was reported that heating ammonium formate with dry GO for several hours results in multi‐layered graphite‐like solid aminated graphene oxide while we obtained processable hydrogels after a minute of bath sonication for reactions employing concentrated GO dispersions.…”
Section: Resultsmentioning
confidence: 80%
“…The Leuckart reaction is a reductive amination process in which aldehydes and ketones are transformed to amines in a multistep reaction that results in reduction of GO and simultaneous incorporation of nitrogen (Scheme ). When ammonium hydroxide is added to GO dispersion, NH 3 ⋅ H 2 O, in equilibrium with NH 4 OH, would transform edge carbonyl groups via a geminal hydroxyamine intermediate to imines in a reversible reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Deconvolution of N 1s using four components with FWHM of 1.5 eV showed peaks positioned at 398.9 eV (N1), 400.0 eV (N2), 400.9 eV (N3), and 402.4 eV (N4). The largest peak (34%), N2, is attributed to either pyrazoline‐like groups originating from hydrazine, or amino/amide groups originating from ammonia . The N1 and N4 peaks were identified as pyridinic‐N (33%) and pyridinic N‐oxide (8%), respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The largest peak (34%), N2, is attributed to either pyrazoline-like groups originating from hydrazine, [58] or amino/amide groups originating from ammonia. [59,60] The N1 and N4 peaks were identified as pyridinic-N (33%) and pyridinic N-oxide (8%), respectively. [61] Finally, the position of peak N3 at 400.9 eV lay between the commonly reported values for pyrrolic-N (400.4 AE 0.3) and quaternary-N (401.3 AE 0.2).…”
Section: Negative Electrode Materialsmentioning
confidence: 99%
“…Graphene can be functionalized with amine groups using the Leuckart reaction, which not only reduces the graphene oxide but leads to a 3.2% amination degree [195]. Other common methods utilized to aminate graphene include nitrogen plasma treatments, chemical vapor deposition, and the reduction of graphene oxide in nitrogen gas or ammonia [196,197].…”
Section: Graphite Graphitic Carbons and Graphenementioning
confidence: 99%